Impikatur dalam Komunikasi Tawar Menawar Antar Penjual dan Pembeli di Pasar Bandar Buat - Shally Amna; Desi Afrianti (Journal on Education, 2023)
Communication between sellers and buyers in Pasar Raya is very frequent and repetitive. This communication tends to cause implicatures. This study aims to analyze and describe the implicatures that appear in conversations between sellers and buyers at the Bandar Buat Market, Padang, West Sumatra. The motivation for conducting this research is the uniqueness and diversity of the characters of sellers and buyers at Pasar Bandar Buat Padang since it is located on the outskirts of the city that accommodates sellers and buyers from various villages with different languages and cultures. The samples of this research were 10 utterances between sellers and buyers. This study used expressive qualitative methods. Data collection used observation, record and record techniques. Based on the results and analysis of research data using Levinson's theory (1994), 10 implicatures were obtained with the various implicatures that appear are contrast implicatures, simplifications and symbolic implicatures.